Impact of shopping emotion towards impulse buying in e-commerce platform - Fajar Destari; Ketut Indraningrat; Maulita Nanda Nilam Putri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This empirical research aims to examine the influence of discount programs, website quality, and online reviews directly and indirectly on the impact of shopping emotion towards impulse buying on the e-commerce website. Data were purposively obtained from a total population of 130 respondents and analyzed using a Structural Equation Model (SEM). The results showed a significant positive effect on discount Programs and Website Quality on impulse buying with shopping emotions as a mediating variable. Besides, the result also showed an insignificant impact on online reviews.